2014
DOI: 10.2188/jea.je20140006
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Screen-Time Among Chinese Adolescents: A Cross-Sectional Study

Abstract: BackgroundRapid urbanization in China has led to a proliferation of electronic entertainment media among youth. Prolonged screen time (ST; includes watching television and playing on computers, video game consoles, or mobile phones) is linked to poor health profiles. The aim of this study was to report recreational ST behaviors and ST correlates among Chinese adolescents living in two regions with different degrees of urbanization.MethodsA cross-sectional, school-based survey (n = 3461 adolescents; aged 12–14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 20 publications
(25 reference statements)
4
40
1
1
Order By: Relevance
“…A recent study reported that 26.1% of adolescents were exposed to screen time for ≥2 h/day in China [ 31 ]. TV viewing and playing on the computer were found to be the most prevalent screen time behaviors among Chinese adolescents [ 32 ]. In our current study, approximately 42.9% of the students reported screen time for ≥2 h/day.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that 26.1% of adolescents were exposed to screen time for ≥2 h/day in China [ 31 ]. TV viewing and playing on the computer were found to be the most prevalent screen time behaviors among Chinese adolescents [ 32 ]. In our current study, approximately 42.9% of the students reported screen time for ≥2 h/day.…”
Section: Discussionmentioning
confidence: 99%
“…As today’s adolescents frequently use MP and other communication tools in their homes, community environments and at school [ 1 ], they have longer exposure time to MP. In 2014, the proportion of adolescents who own MP is more than 60% in Shanghai, China [ 2 ] and still increasing. Additionally, with the increasing use of MP, concerns have been raised in a number of countries about the adverse health effects of MP use on adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a need for exion and even hyper exion of the cervical segments have to increase, as many people use technological devices for recreation or/and work, especially smartphones for hours during the day. In 2014, the proportion of adolescents who used the smartphone was more than 60% in Shanghai, China, and this gure still keeps rising [25]. Therefore, considering the adverse health effects of the increasing prevalence of smartphones on young adults, the present risk analysis of FOC about such an exposure, could be a promising new parameter in predicting CS, which is of great signi cance to spine surgeons.…”
Section: Discussionmentioning
confidence: 99%